Estudo da influência da temperatura de brasagem nas uniões zircônia/aço inox 304 utilizando metalização mecânica - Carneiro, Jaciane Moraísa (2014)
Metal-Ceramic (M/C) Zirconia-stainless steel interfaces have been processed through brazing techniques due to the excellent combination of properties such as high temperature stability, high corrosion resistance and good mechanical properties. However, some M/C interfaces show some defects, like porosity and cracks results in the degradation of the interfaces, leading even to its total rupture. Most of time, those defects are associated with an improper brazing parameters selection to the M/C system. In this work, ZrO2 Y-TZP and ZrO2 Mg - PSZ were joint with the stainless steel grade 304 by brazing using a eutectic silver-copper (Ag28Cu) interlayer alloy with different thermal cycles. Ceramic surfaces were previous mechanically metallized with titanium to improve adhesion of the system. The effect of temperature on the M/C interface was studied. SEM-EDS and 3 point flexural bend test were performed to evaluate morphology, chemical composition and mechanical resistance of the M/C interfaces. Lower thermal cycle temperatures produced better results of mechanical resistance, and more regular/ homogeneous reaction layers between braze alloy and metal-ceramic surfaces. Also was proved the AgCu braze alloy activation in situ by titanium